I Do it My Way: Understanding Policy Variation in Pandemic Response Across Europe - Egger, Clara Marie; Magni-Berton, Raul; Roché, Sebastian; Aarts, Kees (Frontiers in Political Science, 2021)
To contain the spread of the COVID-19, governments have designed and implemented a large range of exceptional measures. Yet, the restrictive nature of the policy options chosen and the severity of their enforcement mechanisms considerably vary across countries. Focusing on the case of the European Union—a group of closely connected nations which develop some forms of supranational policy coordination to manage the pandemic—, we first map the diversity of policy responses taken using two original indicators: the stringency and scope of freedom limitations and the depth of control used in their enforcement. Second, we elaborate three theoretical scenarios to explain cross-national variation in pandemic policy-making. Our exploratory results—based on bivariate statistical associations—reveal that structural determinants (the level of political and interpersonal trust, a country’s overall resources, democratic experience and, to a lesser extent, political check and balances) shape crisis policy-making more than crisis-related factors such as the magnitude of the crisis at stake. These results call for further research into the determinants of crisis policy-making that we propose to address with a new research project focusing on the modalities, determinants and impacts of exceptional decision making in times of COVID-19.